Altered bone metabolism in the protein deprived rat - Le Roith, Derek (Department of Medicine, 2017)
In contrast to the vast amount of active research and available knowledge on many aspects of protein-calorie malnutrition, surprisingly little attention has been focused on the skeletal effects of this syndrome. As early as the 1920's it was realised that the skeletal metabolism in protein-calorie malnutrition was deranged. Notwithstanding this, there is still to date inadequate understanding of the mechanisms by which these skeletal changes are brought about. This is partly due to the fact that the research workers were "victims of their times" in that the techniques utilised gave limited information and it has only been in the past decade or two that more sophisticated techniques have become available. (Evidence for this will be borne out in the following chapter where the literature is reviewed). It was with this in mind that the work presented in this thesis was undertaken. Part I of the thesis consists of a review of the literature, followed by a dissertation on the normal physiological concepts of calcium metabolism as well as a description of the calcium pools used in kinetic models. Part II includes all the chapters on the various experiments performed. Included in each chapter are the methods used, results obtained as well as a discourse relevant to that particular study, with special reference to similar experiments performed by other authors. Part III encompasses the integrated summary of the results and a discussion theorising the mechanisms involved in those changes. Finally, an appendix which deals with the statistical methods used for analyses, as well as details of those techniques which were used, but were established by other authors.